2015
DOI: 10.3389/fpsyg.2015.01229
|View full text |Cite
|
Sign up to set email alerts
|

Phonology without universal grammar

Abstract: The question of identifying the properties of language that are specific human linguistic abilities, i.e., Universal Grammar, lies at the center of linguistic research. This paper argues for a largely Emergent Grammar in phonology, taking as the starting point that memory, categorization, attention to frequency, and the creation of symbolic systems are all nonlinguistic characteristics of the human mind. The articulation patterns of American English rhotics illustrate categorization and systems; the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Taken together, the ERP results reveal that orthographic codes are accessed earlier than phonological codes, which is consistent with a behavioral study (Zhang and Wang, 2015 ) of varied SOAs in a PWI task (see the introduction for details). Several studies on alphabetic languages (e.g., French and English) also found that phonological overlapping did not affect orthographic output in writing (Bonin et al, 1998 ; Roux and Bonin, 2012 ; Shen et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together, the ERP results reveal that orthographic codes are accessed earlier than phonological codes, which is consistent with a behavioral study (Zhang and Wang, 2015 ) of varied SOAs in a PWI task (see the introduction for details). Several studies on alphabetic languages (e.g., French and English) also found that phonological overlapping did not affect orthographic output in writing (Bonin et al, 1998 ; Roux and Bonin, 2012 ; Shen et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
“…Using a PWI task combined with the ERP technique, we explore the time courses of orthographic and phonological codes and their interplay in written word production. The behavioral results exhibit the typical orthographic and phonological facilitation effects, replicating previous results in Chinese (Qu et al, 2011 ; Zhang and Wang, 2015 ). The ERP results reveal that the orthographic relatedness modulates the ERP amplitudes in the time window of 370–500 ms, while the phonological relatedness modulates the ERP amplitudes in the time window of 460–500 ms, reflecting that phonological codes are accessed later than orthographic codes in written production.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…If we dismiss the Chomskyan UG hypothesis and the universal set of distinctive features it contains (in the Hale and Reiss, 2008 view) the structures (syntactic categories, morphosyntactic structure, syllable structure and the internal structure of sounds) that we observe on the basis of linguistic evidence have to come from somewhere else. The typical answer provided by those who reject the innatist view, is that it comes from, or emerges from, language usage rather than being part of UG (Johnson, 1997;Bybee, 2006;van de Weijer, 2014;Van de Weijer, 2017;Archangeli and Pulleyblank, 2015;and many others). Although there are a lot of different usage-based approaches to language, such as, among others, Construction Grammar (cf.…”
Section: Where Does Structure Come From?mentioning
confidence: 99%
“…Emergent Phonology is a relatively recent paradigm in phonological theory, which proposes that units such as distinctive features, segments, words and elements of the prosodic hierarchy such as syllabic constituents and feet, emerge in the course of the acquisition process rather than being stipulated as part of Universal Grammar (UG), here understood as an innate capacity specifically for language (e.g., Bates et al 1998;Beckman & Edwards 2000;Mielke 2008;Archangeli & Pulleyblank 2015;; see also van de Weijer 2009;2012;2014;van de Weijer & Sloos 2013;van de Weijer & Tzakosta 2017, and many others). The question of whether Universal Grammar exists and, if so what it consists of, has had a long and controversial history in modern linguistics, starting with Chomsky (1965).…”
Section: Introductionmentioning
confidence: 99%